The prevalence of urinary tract infections in type 2 diabetic patients: a systematic review and meta-analysis - Salari, Nader; Karami, Mohammad Mahdi; Bokaee, Shadi; Chaleshgar, Maryam; Shohaimi, Shamarina; Akbari, Hakimeh; Mohammadi, Masoud; Daneshkhah, Alireza; Shohaimi, Shamarina (BioMed Central, 2022)
Background: Urinary tract infection is the most common infection in type 2 diabetic patients. Various studies have reported different outbreaks of urinary tract infections in type 2 diabetic patients. Therefore, the present study aimed to determine the prevalence of urinary tract infections in type 2 diabetic patients during a systematic review and meta-analysis in order to develop interventions to reduce the incidence of urinary tract infections in type 2 diabetic patients. Methods: In this study, systematic review and meta-analysis of study data related to the prevalence of urinary tract infection in type 2 diabetic patients were conducted using keywords including type 2 diabetes, urinary tract infection, diabetes, prevalence, meta-analysis and their English equivalents in SID, MagIran, IranMedex, IranDoc, Google Scholar, Cochrane, Embase, Science Direct, Scopus, PubMed and Web of Science (WoS) databases from 1993 to 2020. In order to perform the analysis of qualified studies, the model of random-effects was used, and the inconsistency of studies with the I2 index was investigated. Data analysis was performed with Comprehensive Meta-Analysis (Version 2). Results: Based on a total of 15 studies with a sample size of 827,948 in meta-analysis, the overall prevalence of urinary tract infection in patients with type 2 diabetes was 11.5% (95% confidence interval: 7.8–16.7%). The prevalence of urinary tract infections in diabetic Iranian patients increased with increasing number of years of research, (p < 0.05), and with increasing age of participants (p < 0.05), but however the prevalence decreased with increasing sample size (p < 0.05). Conclusion: This study shows that urinary tract infections are highly prevalent in patients with type 2 diabetes. Therefore, due to the growing prevalence of diabetes and its complications such as urinary tract infections, the need for appropriate screening programs and health care policies is becoming more apparent.